PENINGKATAN PEMAHAMAN HADIS AMALIYAH NAHDLATUL ULAMA MELALUI METODE SERVICE LEARNING PADA SISWA MADRASAH ALIYAH NURUL WAHID AL-WAHYUNI BESUK PROBOLINGGO - Ar Rumi, Ach. Jalaluddin; Fauzen, Muhamad; Nafisah, Lailiyatun (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
Extremism and radicalism are common among teenagers. Not understanding the basis of religion is also one of the causes of intolerance. In this community service, using the service learning (SL) method with the type of direct service with the aim of introducing the traditions of NU amaliyah and providing a strong understanding of the younger generation, especially students at Madrasah Aliyah Nurul Wahid Paiton Probolinggo in an interactive dialog between students and speakers. Awareness of the importance of understanding the basis of this amaliyah is the goal point in this activity. There are three stages in this activity, namely pre-implementation activities, implementation and evaluation of activities. The results of PKM activities at Madrasah Aliyah Nurul Wahid Al-Wahyuni Sumberan Besuk Probolinggo show that this activity can enrich students' knowledge and understanding of the traditions of Nahdlatul Ulama's amaliyah, with the percentage of students who understood the material presented as much as 74.2%, and motivate them to spread the knowledge that NU traditions have a strong basis and evidence in the hadith. As well as for educators in the Nurul Wahid Madrasah Aliyah environment, this activity can be an additional motivation in order to provide creative, innovative and progressive lessons according to the challenges of the times. Keywords: Understanding: Hadith ; service learning